Validation, Optimization, and Application of the Zebrafish Developmental Toxicity Assay for Pharmaceuticals Under the ICH S5(R3) Guideline - Song, Yi-Sheng; Dai, Ming-Zhu; Zhu, Chen-Xia; Huang, Yan-Feng; Liu, Jing; Zhang, Cheng-Da; Xie, Feng; Peng, Yi; Zhang, Yong; Li, Chun-Qi; Zhang, Li-Jiang (Frontiers in Cell and Developmental Biology, 2021)
The zebrafish as an alternative animal model for developmental toxicity testing has been extensively investigated, but its assay protocol was not harmonized yet. This study has validated and optimized the zebrafish developmental toxicity assay previously reported by multiple inter-laboratory studies in the United States and Europe. In this study，using this classical protocol, of 31 ICH positive compounds, 23 compounds (74.2%) were teratogenic in zebrafish, 5 had false negative results, and 3 were undefinable; of 14 ICH negative compounds, 12 compounds (85.7%) were non-teratogenic in zebrafish and 2 had false positive results. After we added an additional TI value in the zebrafish treated with testing compounds at 2 dpf along with the original 5 dpf, refined the testing concentration ranges, optimized the TI cut-off value from ≥ 10 to ≥ 3 for compounds with refined testing concentrations, and proposed a new category as the undefinable compounds for those TI values smaller than the cut-off both at 2 dpf and 5 dpf but inducing toxic phenotypes, this optimized zebrafish developmental assay reached a 90.3% sensitivity (28/31 positive compounds were teratogenic in zebrafish) and 88.9% (40/45) overall predictability. Our results from this study strongly support the use of zebrafish as an alternative in vivo method for screening and assessing teratogenicity of candidate drugs for regulatory acceptance.